Homozygous variegate porphyria: an evolving clinical syndrome. Issue 816 (October 1993) - Hift, R. J.; Meissner, P. N.; Todd, G.; Kirby, P.; Bilsland, D.; Collins, P.; Ferguson, J.; Moore, M. R.
Abstract : Variegate porphyria is one of the most frequently encountered genetic conditions in South Africa. It is inherited as an autosomal dominant disease and in excess of 300 heterozygous cases have been studied by the Cape Town unit. Despite this, the homozygous condition has not previously been encountered in South Africa. We report two cases of homozygous variegate porphyria, one of whom represents the first South African case. We delineate a syndrome principally characterized by growth retardation, developmental delay, epileptic seizures, photosensitivity and an abnormal porphyrin excretion pattern. In addition we describe, in one case, two features not previously reported: skin disease in areas unexposed to light and a severe sensory neuropathy which may account at least in part for the hand deformities of this disorder.